Identification of the Suitability of Facilities and Infrastructure of Allu Traditional Market Based on Indonesian National Standard of Traditional Market - Milda Apriliana (Journal of Agribusiness and Natural Resources, 2025)
Allu Market is one of the markets in Bangkala District which has a strategic location because it is on the jeneponto-takalar axis road. Based on the results of pre-research conducted by the Allu Traditional Market in Bangkala District, Jeneponto Regency, there are still limited facilities and infrastructure that cause the influence on consumer or public interest in visiting the market to be reduced so that researchers are interested in researching the suitability of the Allu Traditional Market Facilities and Infrastructure Based on the People's Market SNI. The research method used uses descriptive-qualitative analysis method. The results showed that it can be concluded that the level of conformity of Allu Market facilities and infrastructure with SNI 8152: 2015 standards reached 44.11%, while those that were not suitable were 55.88%. This shows that the facilities and infrastructure in Allu Market are still classified as not suitable.